Islamicity Performance Index Dan Struktur Modal Terhadap Kinerja Keuangan Perbankan Syariah - Anggita Putri Pratiwi; Yadi Nurhayadi; Mulyaning Wulan (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
Today's sharia-based finance has grown rapidly. One of them is a sharia-based bank financial institution that has begun to develop from time to time, in terms of assets and performance. The bank is said to be healthy if it produces satisfactory performance. Your research discusses the relationship between the Islamicity performance index as the first variable consisting of profit sharing and zakat and the second variable consisting of the capital structure of Islamic banking on the performance of Islamic banking. The research method used is descriptive associative quantitative method which explains the relationship between the variables with each other. Partially profit sharing and capital structure have no effect and zakat has a negative effect on financial performance. Simultaneously there is an influence between profit sharing, zakat and capital structure on the financial performance of Islamic banking. The regression model shows an adjusted r-square value of 0.201. This shows that the profit sharing ratio, zakat performance ratio and capital structure can explain 20.1% of the dependent variable, namely the financial performance (ROA) of Islamic banking.